Role-Play in Language Learning: A Bibliometric Analysis and its Impact on Thailand Secondary Education - Kongsaenkham, Ananta; Chano, Jiraporn (Journal of Language Learning and Assessment, 2024)
Purpose This study investigates the trends, challenges, and pedagogical implications of role-play as a method for English language learning in Thai secondary schools. Methodology Utilizing bibliometric analysis, 800 publications from 2019 to 2024 were analyzed to identify research patterns and thematic developments. Results/Findings The results reveal a consistent decline in research output, with the highest number of publications recorded in 2019 and 2020 (170 articles each), followed by a significant decrease in subsequent years. The bibliometric analysis identified 44 key terms distributed across six thematic clusters, emphasizing areas such as communication skills, student engagement, and interdisciplinary applications. Despite the declining research focus, role-play remains an effective pedagogical tool for enhancing English speaking proficiency, fostering authentic communication, and building learner confidence. However, its implementation in Thai secondary schools faces challenges, including traditional teacher-centered approaches, large class sizes, and limited resources. To address these challenges, this study highlights the potential of integrating modern technologies, such as virtual and augmented reality, into role-play activities to enhance accessibility and engagement. Furthermore, it underscores the importance of adopting performance-based assessments to evaluate students’ progress more effectively. Implications This research contributes to the understanding of role-play's enduring relevance and offers practical recommendations for its revitalization in language education. By addressing existing barriers and leveraging innovative approaches, role-play can remain a transformative strategy for fostering English language proficiency and student engagement in Thai secondary school contexts.